A REALISTIC VIEW: FUNCTIONS OF ANOTHER LANGUAGE - Sivell, John N. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1983)
Second-language teaching is almost a major industry at universities all over the world, although it is conducted with a peculiar intensity in linguistica1ly sensitive situations like Quebec’s. Sivell has taught in the Middle East, Morocco, and Ontario, and makes here what may strike some as a fairly simple point about practice in the prevailing doctrine that one should teach communication functionally. The communication functions in a second language expected of a university student, though familiar to us all, are by no means always those assumed by the doctrinaire. As always with motivation - that critical element - neglect of a simple point can bring down the whole edifice of a curriculum. RÉSUMÉ L’enseignement des langues secondes constitue pratiquement une industrie dans la plupart des universités du monde, même s’il se pratique avec une intensité toute particulière dans les milieux linguistiquement fragiles comme le Québec. Sivell a enseigné au Moyen-Orient, au Maroc et en Ontario et il affirme ici, ce qui pourra paraître relativement simpliste à certains, que l’on doit enseigner la communication de manière fonctionnelle. Les fonctions de communication d’une langue seconde que l’on attend d’un étudiant d’université, même si elles nous sont familières, ne sont pas toujours celles que présuppose le doctrinaire. Comme toujours avec la motivation, cet élément crucial, l’oubli d’un simple élément peut entraîner l’effondrement de tout l’édifice d’un program.